Influence of ORM1, PXR, CAR, CYP3A4 and CYP3A5 gene polymorphisms in mediating susceptibility risk to chronic myeloid leukaemia and response to imatinib mesylate therapy - Maddin, Najlaa (2017)
Genetic polymorphisms are well recognized sources of individual differences in disease risk and treatment response. Associations between human genetic variants and predisposition to diseases and adverse events for different kinds of drug interactions with hundreds of protein like receptors, transporters and metabolizing enzymes have been described. Chronic myeloid leukaemia (CML) is a myeloproliferative disorder for which the molecular targeted drug Imatinib mesylate (IM), is the gold standard drug. Despite its excellent efficacy, resistance to IM emerges in a significant number of CML patients. Development of resistance could be due to several factors. Pharmacokinetic variability as a result of genetic polymorphisms in IM metabolizing genes could be a potential factor. This study was undertaken in a total of 540 subjects [270 CML patients (139 IM resistant and 131 IM good responder) and 250 normal healthy controls] to investigate the genotype frequencies and the impact of ORM1 520G>A, PXR 1792A>G, CAR 540C>T, CYP3A4 878T>C and CYP3A5 6986A>G polymorphisms towards CML susceptibility risk and IM response. Genotyping was performed by using three methods, DNA sequencing, Polymerase Chain Reaction – Restriction Fragment Length Polymorphisms (PCR-RFLP) and Allele Specific – PCR (AS-PCR) technique. The genotypes were categorized into homozygous wild type, heterozygous and homozygous variant genotype. The association between allelic variants and CML susceptibility riskand response to IM treatment were assessed by means of odds ratio (OR) with 95% confident intervals calculated by logistic regression. Results showed absence of homozygous variant genotype of CYP3A4 878T>C and ORM1 520G>A in both CML patients and normal healthy controls. When the association of genotypes with CML susceptibility risk was assessed, polymorphisms 520G>A of ORM1 and 1792A>G of PXR showed no significant associations with CML susceptibility risk. Whereas, the homozygous variant (TT) genotypes of CAR 540C>T (OR 3.638; 95% CI: 1.779-7.623, p<0.001) and the heterozygous (TC) genotype of CYP3A4 878T>C (OR 3.387; 95% CI: 1.433-8.007, p=0.005) were significantly associated with CML susceptibility risk. In contrast, both heterozygous (AG) and homozygous variant (GG) genotype of CYP3A5 6986A>G showed protective effect for susceptibility to CML (OR 0.310; 95% CI: 0.180-0.535, p<0.001 and OR 0.140; 95% CI: 0.079-0.246, p<0.001, respectively). Next, when the associations of genotypes with IM response in CML patients were evaluated, the SNPs ORM1 520G>A and CYP3A4 878T>C were not significantly associated with IM response. But, both heterozygous and homozygous variant genotypes of PXR 1792A>G (OR 2.769; 95% CI: 1.290-5.943, p=0.007 and OR 2.632; 95% CI: 1.030- 6.723, p=0.041, respectively) and CAR 540C>T (OR 2.700; 95% CI: 1.116-6.536, p=0.028 and OR 2.923; 95% CI: 1.156-7.393, p=0.023, respectively) showed significant association with IM resistance in CML patients. However, CML patients with heterozygous (AG) and homozygous variant (GG) genotypes of CYP3A5 6986A>G (OR 0.171; 95% CI: 0.090-0.324, p<0.001 and OR 0.257; 95% CI: 0.126-0.525, p<0.001, respectively) showed significant association with IM good response to IM. Finally, when the risk was evaluated based on the combination of genotypes, a few combinations were associated with IM good response and a few others with IM resistance. Although a fewgenotypes associated with susceptibility risk and IM response in CML patients were observed, further studies are warranted on a larger scale to validate whether these polymorphisms could be used as predictive biomarkers